إطالة عمر شبكات الحساسات اللاسلكية المعتمدة على بروتوكول ZigBee - خليفة جمال (Latakia University Journal -Engineering Sciences Series, 2016)
يلعب تخفيض استهلاك الطاقة للعقد المختلفة في شبكات الحساسات اللاسلكية دوراً هاماً وأساسياً في إطالة عمر هذه الشبكات. وكي لا يكون استهلاك الطاقة في بعض العقد كبيراً، وفي بعض العقد أقل، أو حتى صغيراً، فإن اختيار خوارزميات توزيع أدوار العقد، بين عقد طرفية، وعقد توجيه، وتبديل هذه الأدوار، يلعب دوراً هاماً في إطالة عمر شبكات الحساسات اللاسلكية. يقدم هذا البحث خوارزمية لتوزيع الأدوار بما يسمح بتشكيل نماذج شجرية متعددة لشبكة واحدة. وهذا يقدم الإمكانية لمنسق الشبكة بتبديل أدوار العقد مركزياً بتبديل النموذج الشجري كلما دعت الحاجة حسب مؤشرات استهلاك الطاقة في العقد. وتظهر النتائج أن استخدام الخوارزمية يؤدي إلى تحسن كبير في زمن حياة الشبكة يتراوح بين 2 و 4 مرات، وذلك حسب السماح بنوم واستيقاظ العقد أو عدم السماح بذلك. وذلك من أجل معدلات إرسال مختلفة. وقد تم اختبار سيناريوهات عمل شبكات الحساسات اللاسلكية بالاعتماد على استخدام تقنية ZigBee، وباستخدام المحاكاة، اعتماداً على المحاكي الشبكي NS-2. The reducing of energy consumption for various nodes in wireless sensor networks plays an important and essential role in the prolonging of the life of these networks. In order not to be the energy consumption in some node is very high and in others is less or very low, the choice of distribution algorithms of the nodes role, as a router node or terminal nodes, and switching between them, plays an important role in prolonging the lifetime of wireless sensor networks. This paper presents an algorithm for the distribution of WSN nodes roles, including allowing the applying of many tree patterns to a single network. This offers the potential to alter the network nodes roles centrally by coordinator and switching between these tree patterns whenever the need arises according to the indicators of energy consumption in the nodes. The results show that the use of the algorithm leads to a significant improvement in the network life ranges between 2 and 4 times, according to the allowing the nodes to sleep and wakeup, or not, for different transmission rates where the scenarios have been tested for ZigBee based wireless sensors networks using NS-2 simulator.